INTERNATIONAL LEGAL COOPERATION IN THE FIELD OF PREVENTION AND SUPPRESSION OF ILLEGAL SEIZURE, TRAFFICKING AND TRANSPLANTATION OF HUMAN ORGANS - Charоskhоn Numоnоva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The illegal organ trade thrives in the shadows, exploiting vulnerable individuals and jeopardizing public health. This article delves into the effectiveness of international legal cooperation in dismantling these criminal networks. We analyze key legal instruments such as the UNTOC and regional conventions, exploring their strengths and limitations in fostering international collaboration. We further examine national legislation across diverse countries, identifying gaps and inconsistencies in combating this global threat. By dissecting the challenges hindering effective cooperation, the article proposes concrete recommendations to build a more robust international response. This includes improved information sharing, enhanced law enforcement collaboration, and promoting ethical practices in organ donation. This timely article is a call to action for policymakers, legal professionals, and healthcare systems to strengthen the global fight against the illegal organ trade.